Social Participation of People With Disabilities Though the Activities of Non – Governmental Organizations - Beneševičiūtė, Irmina (Pedagogika, 2014)
Due to the change of social paradigm in society and intensive processes of social integration and socialization, the issue of social participation of the disabled has become relevant. Therefore, based on subjective experience of the disabled, this publication, aims to present research results on social participation of disabled individuals through NGO activities, their potential, areas of activity development. Aim of the research: to reveal social participation development directions at nongovernmental disability organisations. This quantitative research had various nongovernmental disability organisations participating from various cities and regions, in total of 18 individuals that are active participants at NVO activities. The age scope of the respondents was 25 to 70 years old. Research results: factors that encourage the cooperation of the disabled in NGO activities – negative disabled experiences and emotions of solitude with answering the necessity to communicate at NGO. During the analysis of social participation possibilities that are available to the disabled with the immersion into NGO activities, the disabled had identified that the socio-cultural participation of the disabled and interest representation was the key area of NGO activities. The research, by applying qualitative research methodology, revealed that the participants, in regard to the activity prospects of NGO, stressed the priority of financial base strengthening while pursuing project activities. The research also revealed a positive tendency of hope for future educational activity. Though these educational activities the disabled will further develop their expertise and expand their knowledge of disability. However there was little focus, among research participants, on competent expert immersion into NGO, where the need for positive encouraging of the disabled is also of high importance.